Communicating diagnoses to individuals with a first episode psychosis: A qualitative study of individuals perspectives - Huurman, Marina Elisabeth; Pijnenborg, Gerdina Hendrika Maria; Sportel, Bouwina Esther; van Rijsbergen, Gerard David; Hasson-Ohayon, Ilanit; Boonstra, Nynke (Frontiers in Psychiatry, 2023)
Background Receiving the label of a psychotic disorder influences self-perception and may result in negative outcomes such as self-stigma and decreased self-esteem. The way the diagnosis is communicated to individuals may affect these outcomes. Aims This study aims to explore the experiences and needs of individuals after a first episode of psychosis with regard to the way in which information about diagnosis, treatment options and prognosis is communicated with them. Design and methods A descriptive interpretative phenomenological approach was used. Fifteen individuals who experienced a first episode of psychosis participated in individual semi-structured open-ended interviews on their experiences and needs regarding the process of providing information about diagnosis, treatment options and prognosis. Inductive thematic analysis was used to analyze the interviews. Results Four recurring themes where identified (1) timing (when); (2) content (what); and (3) the way information is provided (how). Individuals also reported that the provided information could elicit an emotional reaction, for which they would require specific attention, therefore the fourth theme is (4) reactions and feelings. Conclusion This study provides new insights into the experiences and specific information needed by individuals with a first episode of psychosis. Results suggest that individuals have different needs regarding the type of (what), how and when to receive information about diagnosis and treatment options. This requires a tailor-made process of communicating diagnosis. A guideline on when, how and what to inform, as well as providing personalized written information regarding the diagnosis and treatment options, is recommended.